The Effectiveness of Systematic Desensitization Techniques in Lowering Post-Breakup Anxiety in Senior High School Students - Nisa', Fina Yurotun; Farid, Dimas Ardika Miftah (STAI Auliaurrasyidin Tembilahan, 2025)
Post-breakup anxiety among adolescents, if not properly addressed, can lead to significant emotional disruption and hinder psychological development. Breakups often trigger a range of negative emotional responses, including sadness, anxiety, and a decline in self-esteem. For adolescents, particularly students, these emotional disturbances may result in diminished concentration, reduced academic performance, and impaired personal growth. This study aimed to evaluate the effectiveness of systematic desensitization techniques in alleviating post-breakup anxiety among high school students. Utilizing a pre-experimental research design with a one-group pre-test and post-test approach, the study involved a population of 128 students from four classes at Intensif Taruna Pembangunan Surabaya Senior High School. From this population, six students who met specific criteria were selected through purposive sampling. Data were collected using a 36-item breakup anxiety scale based on a 4-point Likert format, administered via Google Forms. Statistical analysis was conducted using the Wilcoxon signed-rank test to compare pre- and post-intervention scores. The results indicated a statistically significant reduction in post-breakup anxiety following the intervention, with an Asymp. Sig. (2-tailed) value of 0.027 (p < 0.05). These findings suggest that systematic desensitization is an effective therapeutic technique for managing emotional distress related to romantic relationship dissolution in adolescents. The study highlights the importance of incorporating behavioral interventions into school-based counseling services. Future research is recommended to include a broader and more diverse population, such as students from different educational levels and cultural contexts, or to explore the combined efficacy of systematic desensitization with other counseling approaches.